Correlation of Quantitative Assay of HBsAg and HBV DNA Levels During Chronic HBV Treatment - (:unkn) unknown (SPRINGER, 2008)
Background and aim Viral load is used for the diagnosis and monitoring the treatment of chronic hepatitis B (CHB). These methods are molecular-based and are expensive. Previous studies suggest that quantitative hepatitis B surface antigen (HBsAg) studied by automated chemiluminescent microparticle immunoassay can be a surrogate marker. In this study, we aimed to investigate whether quantitative HBsAg correlates hepatitis B virus (HBV) DNA levels during CHB treatment. Methods The study included 18 patients (13 male, 5 female, mean age: 33 +/- 9 years) with CHB. They were given pegylated interferon +/- lamivudine for 52 months and serum samples were obtained in weeks 0, 4, 8, 24, 48, 52, and 76. HBV DNA was measured by TaqMan polymerase chain reaction (PCR; Erasmus MC, University Medical Center, Rotterdam, The Netherlands). Quantitative HBsAg was studied by automated chemiluminescent microparticle immunoassay (Architect HBsAg, Abbott, IL). Results HBV DNA levels were measured as follows: 9.66, 7.69, 7.06, 5.93, 5.89, 5.88, and 7.27 logarithmic genome equivalent/ml, respectively. The corresponding HBsAg quantitation results were 42,888, 31,176, 37,882, 27,277, 28,279, 29,471, and 31,535 IU/ml, respectively. They showed a significant correlation (canonical correlation = 0.85). Conclusions HBsAg studied by automated chemiluminescent microparticle immunoassay correlates with HBV DNA and can be a surrogate marker during the monitoring of the efficacy of HBV treatment.
Keywords: Chronic hepatitis B; HBsAg quantitation; Automated chemiluminescent microparticle immunoassay; CHRONIC HEPATITIS-B; CHEMILUMINESCENT MICROPARTICLE IMMUNOASSAY; SURFACE-ANTIGEN; VIRUS CARRIERS; LAMIVUDINE; TRIAL